LANGUAGE TEACHING IN VIEW OF POSTMODERN PARADIGM - Surya Asra; Chairuddin Chairuddin; Fiza Rauzika Altasa; Pangkuh Ajisoko (Universitas Islam Sumatera Utara, 2022)
The postmodern paradigm has developed very broadly. It has not only become a discussion in the field of philosophy but also influenced almost all fields of science, especially the socio-cultural sciences, including language teaching. This study aims to review how postmodernism affects language teaching and what effects it has on the language teaching and learning process, be it teaching a second or foreign language or teaching a first language. This is an analytic study using a literature review approach from written sources to describe the results and draw research conclusions. The results show that postmodernism has influenced language teaching, especially with the emergence of criticism of existing teaching methods and the raising of the critical question of whether teaching languages should use existing teaching methods or whether language teaching does not need to follow these methods. Criticism then gives birth to an understanding method of pedagogy that is based on communicative language teaching (CLT). Postmodern philosophy suggests that language teaching can be done with a combination of several existing methods or can also add new methods or techniques.